2001
DOI: 10.1002/1521-4028(200112)41:6<363::aid-jobm363>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a thermostable and solvent stable extracellular lipase from aPseudomonas sp. AG-8

Abstract: An extracellular lipase isolated from Pseudomonas sp. AG‐8, had an optimal activity at 45 °C and pH 8.0–8.5. It retained more than 80% of its initial activity after keeping for 1 h at 65 °C. The enzyme was stable in 5 M NaCl and 6 M urea. Triton X‐100 increased the lipase activity by 2.4 fold. Ca2+ ions activated the enzyme, while Zn2+, Fe2+, Fe3+ strongly inhibited its activity. Ethanol, methanol and acetone at 20% (v/v) enhanced the lipase activity by 2.9, 3.6 and 4.5 fold respectively. Dimethylsulphoxide at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The lipase from Pseudomonas sp. AG-8 was optimally active at 45 °C and the half life was 5 min at 70 °C (SHARMA et al 2001). Bacillus stearothermophilus L1 lipase was optimally active at 60 -65 °C (KIM et al 1998).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The lipase from Pseudomonas sp. AG-8 was optimally active at 45 °C and the half life was 5 min at 70 °C (SHARMA et al 2001). Bacillus stearothermophilus L1 lipase was optimally active at 60 -65 °C (KIM et al 1998).…”
Section: Resultsmentioning
confidence: 97%
“…It retained more than 80% activity with Co 2+ , Ni 2+ and Pb 2+ and the activity was strongly inhibited by Cu 2+ and Hg 2+ . SHARMA et al (2001) reported inhibition of Pseudomonas sp. AG-8 lipase by Hg 2+ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This property is similar to the extracellular lipase from a Pseudomonas sp. AG-8, it shows 4.5-fold enhanced lipase activity with 20% (v/v) acetone (Sharma et al 2001). For stepwise precipitation the method involved using acetone at different saturations (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Microbial lipase production is usually carried out using submerged fermentation technique [9], however solid state fermentation methods have also been found to be beneficial [10]. Lipid carbon sources have been found to be generally important for obtaining a high lipolytic enzyme yield although a few researchers have obtained substantial lipase yields without using fats or oils [4].…”
Section: Introductionmentioning
confidence: 99%